India's battlefields; from Kurukshetra to Balakot - Singh, Ajay; Naik-Singh, Monishs ed. (New Delhi Pentagon Press, 2020)
An account of 42 of India's battles, right from the epic battle of Kurukshetra fought over 3000 years ago, down to the present day. Virtually every battle of India$1 (Bs vast history has been depicted in its pages. Each battle comes alive as an individual story, complete with maps and pictures. The battles have been cross-referenced so as to establish the thread in the canvas of Indian history. Human interest stories and vignettes are sprinkled to provide unknown insights of these battles. Visit these battlefields and discover the stories they tell.s
Keywords: Security Sector; National Security; Military Operation- Kurukshetra to Balakot